Perancangan Aplikasi E-Modul Berbasis Android untuk Pelajaran Animasi 2D dan 3D - Rahmad Surya; Hendri Ahmadian; Ridwan Ridwan; Khairan AR; Sri Wahyuni; Bustami Bustami (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
This study has the aim of designing an Android-based 2D and 3D animation e-module application which will later become a source of learning for students and also determining the feasibility level of the 2D and 3D animation e-module application to improve student learning outcomes. This study uses research and development (R & D) research methods and uses the Luther development model in developing software engineering applications using MIT App Inventor. This type of research is in the form of quantitative research in which all data is obtained through questionnaires from media experts, material experts, and students, as well as the results of pre-test and post-test students. The respondents in this study were 11 students in Class XI multimedia animation lessons in 2D and 3D. The hypothesis was tested using a paired t-test. The study's findings revealed that the use of 2D and 3D animation e-module applications had significant an impact on improving student learning outcomes.